2010
DOI: 10.1093/beheco/arq023
|View full text |Cite
|
Sign up to set email alerts
|

The responses of prey fish to temporal variation in predation risk: sensory habituation or risk assessment?

Abstract: Predation is an important selection pressure acting on prey behavior. Although numerous studies have shown that when predation risk is high, prey tend to increase vigilance and reduce foraging effort, until recently, few studies have looked at how temporal patterns of risk influence the trade-off between foraging and antipredator behavior. The risk allocation hypothesis predicts that prey should respond strongly to predators that are usually absent, as they can meet their energy demands during safe periods. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Empirical studies have attributed reduced vigilance in systems with a high predator population to prey differential adaptive decision-making in response to complex cues (Barros et al 2008;Ferraria et al 2010). What we observed in the North Fork, where elk response to impediments alone was not significant (Table 5), was similar to the above studies.…”
Section: Discussionsupporting
confidence: 87%
“…Empirical studies have attributed reduced vigilance in systems with a high predator population to prey differential adaptive decision-making in response to complex cues (Barros et al 2008;Ferraria et al 2010). What we observed in the North Fork, where elk response to impediments alone was not significant (Table 5), was similar to the above studies.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, if predators are omnipresent, prey might need to forage actively even though predators are present. Studies with rainbow trout (Mirza et al 2006), convict cichlids (Foam et al 2005b;Brown et al 2006b;Ferrari et al 2010a), guppies (Poecilia reticulata, Poeciliidae; Brown et al 2009b) and several flatfishes (Boersma et al 2008) provide at least partial support for the risk allocation model.…”
Section: Assessing Risk In Timementioning
confidence: 99%
“…Ecology has traditionally considered the importance of spatial variation in predation risk [13], but studies of temporal variation were quite limited until the publication of Lima & Bednekoff's [5] landmark paper on risk allocation. This model proposed that recent background level of risk is a key factor determining the intensity of responses of animals to cues of known predators and has received considerable empirical support [12,14,15]. Recently, Brown et al [16] have also shown that recent background level of risk can promote plasticity in the way animals respond not only to predators, but also to unknown, novel cues in their environment.…”
Section: Introductionmentioning
confidence: 99%